Michael Glykas and the three royal murderers - Varvara Zharkaya (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
Michael Glykas is best known as the author of a vast Chronicle covering the historical events from Creation to the death of the emperor Alexios I Komnenos (1118 AD). Although quite popular in Byzantium, this literary work does not enjoy high reputation among the scholars, the reason being its loose composition and massive uncritical borrowings from earlier sources with only feeble attempts to rework and harmonise them. However, in his other text, a collection of admonitory and dogmatic letters usually referred to as the Theological Chapters, Glykas appears to be an apt storyteller who produces a tightly-knit narrative with rhetorical sophistication and mastery in portraying his heroes’ emotions and in creating suspense. The discrepancies between the two working methods become most visible when the Chronicle and the Theological Chapters deal with the same subjects. This article provides a close reading of the three stories about murders committed by the emperors Theodosios I the Great (379–395), Maurikios (582–602), and Ioannes I Tzimiskes (969–976). These are described in the Chronicle and in the 57th Theological Chapter. The latter was initially conceived as a conciliatory letter addressed to the niece of the emperor Manuel I Komnenos (1143–1180) Theodora, who had committed a murder because of jealousy and was seeking repentance. The analysis shows that the parallel accounts have common compositional structure and share the same set of sources; neither of the two versions contains any unique historical data absent from the other. Nevertheless, the specifi c narrative techniques chosen by Glykas to tell the same stories twice are diametrically opposed to each other. For Glykas as a chronicler, no historical detail is more important than the other, therefore he produces a kind of encyclopaedia cemented by chronology but virtually devoid of narrativity and inner hierarchy. Glykas as an epistolographer, by contrast, has a clear understanding of how to arrange the stories, elaborates their composition, manipulates the reader through key-phrases and syntactical devices, builds drama and makes his characters live through severe breakdowns and then recover before the readers’ eyes. The article proposes to see in Glykas’ unwillingness to narrate coherent stories in the Chronicle a conscious authorial choice motivated by his understanding of chronicle-writing as an activity which is by defi nition opposed to storytelling.